Internet of Things technologies in cardiovascular diseases diagnostics: Literature review and proposal - J. Srinivasan Prasath (Heart Vessels and Transplantation)
Objective: Heart diseases occur for various age groups and the huge percentage of people lost their life due to the heart disease. Heart attack occurs regardless of age and it leads to the death. The aim of the study is to propose the Internet-of Things based electrocardiogram (ECG) monitoring system that can be used for detection of heart disease.